2020
DOI: 10.1016/j.livsci.2020.104057
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ representations of the effects of precision livestock farming on human-animal relationships

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…Indeed, Tallet et al (2019) showed that piglets which were tail docked with a cautery iron interacted with unfamiliar humans later than piglets that were not tail docked, and Lürzel et al (2015) observed that calves avoidance distances were higher after disbudding. In their study, Kling-Eveillard et al (2020) found that following the implementation of PLF, some farmers perceived the HAR as having improved, while others believed it deteriorated. They also mentioned concerns that having to manage an increased amount of data may reduce the time farmers spend with animals and impact farmers' observational skills.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Tallet et al (2019) showed that piglets which were tail docked with a cautery iron interacted with unfamiliar humans later than piglets that were not tail docked, and Lürzel et al (2015) observed that calves avoidance distances were higher after disbudding. In their study, Kling-Eveillard et al (2020) found that following the implementation of PLF, some farmers perceived the HAR as having improved, while others believed it deteriorated. They also mentioned concerns that having to manage an increased amount of data may reduce the time farmers spend with animals and impact farmers' observational skills.…”
Section: Discussionmentioning
confidence: 99%
“…Precision livestock farming lifts off a large amount of repetitive tasks off the farmer (Kling-Eveillard et al, 2020), but brings up new challenges and the need for specialist knowledge, skills and advisory support in order to control and interpret the machineries (Schillings, Bennett and Rose, 2021). PLF might also reduce the farmer's autonomy as they are getting more and more dependent on technological devices, drastically shifting what the job involves and changing farmer identity (Klerkx, Jakku and Labarthe, 2019;Kling-Eveillard et al, 2020;Pol et al, 2021). It has therefore been highlighted by the farmers that the decision making process should still be done by the farmer itself and PLF should only function as a useful guiding tool (Hartung et al, 2017).…”
Section: Implications Of Precision Livestock Farming For the Farmersmentioning
confidence: 99%
“…A shift to relying on automation for monitoring animals as well as for performing physically demanding and repetitive work related to caregiving could lead to a radical paradigm shift in livestock sector priorities, drifting away human-animal interactions as a dominant feature at the core of farming. Using fully-automated technology to complete more husbandry tasks on livestock and poultry farms will change the nature of work on farms and could have impacts on how and how often farmers interact with their animals (Hartung et al, 2017;Kling-Eveillard et al, 2020). Research will be needed to more completely understand the questions that will arise in response to such changes in human-animal interactions, including:…”
Section: Introductionmentioning
confidence: 99%